Effect of Kutaki (Picrorhiza Kurroa Royle Ex Benth) on Dyslipidemia: Life Sciences -Ayurveda - Misar Wajpeyi, Dr.Sadhana; Wajpeyi, Dr. Ketki (International Journal of Life Science and Pharma Research, 2023)
Dyslipidemia is a lifestyle disorder related to a metabolic disorder of lipoprotein metabolism. It is mainly characterizedby raised (TCH) total cholesterol, low-density lipoprotein (LDL) cholesterol, triglyceride (TG) levels, and a fall in the high-densitylipoprotein (HDL) cholesterol levels. It is the key contributing cause of atherosclerosis, coronary artery ailment, andcerebrovascular disease. It can be equated with medodushti and included under Santarpanjanya vyadhi as “Medoroga. This studyassesses the effect of Kutaki (Picrorhiza kurroa Royle ex Benth) on Dyslipidemia. A total of 30 patients with Dyslipidemia weretreated with Kutaki tablets 500 mg twice a day before meals with lukewarm water for 60 days. They were assessed for Lipid levels,Fasting glucose level, AST, ALT, S.Creatinine, and Serum Urea on days 0, 30, and 60. Significant improvement was observed in allparameters after the completion of treatment. Tikta Rasa (bitter taste), Ushna Virya (hot potency), Agnideepan, Pachana, and Lekhanaproperties of Kutaki help break Samprapti. Active ingredients of Kutaki possess Hypolipidemic and choleretic properties, whichhelp correct Lipid levels. Hepatoprotective and nephroprotective properties help in maintaining liver and kidney functionsnormally. It helps in improving deranged Agni and constipation. Kutaki can be useful in treating Dyslipidemia with any side effects.